How do you solve ${\log _5}(x - 1) + {\log _5}(x - 2) - {\log _5}(x + 6) = 0$?
Answer
Verified
438k+ views
Hint:Use log properties to solve the given equation
The very first step to solve these types of problems is to use the addition and subtraction log properties. We know that $\log a + \log b = \log (ab)$ and $\log a - \log b = \log \dfrac{a}{b}$. So, after using the given properties on the above question, we will get a much simplified version of the question. To move forward we will use the $\log a - \log b = \log \dfrac{a}{b}$ property and then move forward to equate the argument part inside the equation to 0. Solving the equation we will get our final answer.
Complete step by step solution:
The given question we have is ${\log _5}(x - 1) + {\log _5}(x - 2) - {\log _5}(x + 6) = 0$
Now, we will use a simple property of log, and that is
$\log a - \log b = \log \dfrac{a}{b}$
So, applying this rule to the question, the modified version of the question will be:-
$
{\log _5}(x - 1) + \left[ {{{\log }_5}(x - 2) - {{\log }_5}(x + 6)} \right] = 0 \\
{\log _5}(x - 1) + \left[ {{{\log }_5}\left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
$
Now, we will use another log property which states that:-
$\log a + \log b = \log (ab)$
So, when we use this property, our modified version of the question will be:-
$
{\log _5}(x - 1) + \left[ {{{\log }_5}\left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\left( {x - 1} \right) \times \left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\dfrac{{\left( {x - 1} \right)\left( {x - 2} \right)}}{{x + 6}}} \right] = 0
\\
\Rightarrow {\log _5}\left[ {\dfrac{{{x^2} - 2x - x + 2}}{{x + 6}}} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\dfrac{{{x^2} - 3x + 2}}{{x + 6}}} \right] = 0 \\
$
To further simplify this step, we will use another property which states that:-
If,
$
{\log _b}a = x \\
\Rightarrow {b^x} = a \\
$
So, if we use this property on the above question, we will get:-
\[
{\log _5}\left[ {\dfrac{{{x^2} - 3x + 2}}{{x + 6}}} \right] = 0 \\
\Rightarrow {5^0} = \dfrac{{{x^2} - 3x + 2}}{{x + 6}} \\
\Rightarrow 1 = \dfrac{{{x^2} - 3x + 2}}{{x + 6}} \\
\Rightarrow x + 6 = {x^2} - 3x + 2 \\
\]
Subtracting x from both the sides we will get:-
\[
x + 6 = {x^2} - 3x + 2 \\
x + 6 - x = {x^2} - 3x + 2 - x \\
6 = {x^2} - 4x + 2 \\
\]
Subtracting 2 from both the sides we will get:-
\[
6 = {x^2} - 4x + 2 \\
6 - 2 = {x^2} - 4x + 2 - 2 \\
4 = {x^2} - 4x \\
\]
Subtracting 4 from both the sides we will get:-
\[
4 = {x^2} - 4x \\
4 - 4 = {x^2} - 4x - 4 \\
{x^2} - 4x - 4 = 0 \\
\]
To solve this step we will use the quadratic formula method \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
Here,
a=1
b=-4 and c=-4
so,
\[
x = \dfrac{{ - ( - 4) \pm \sqrt {{{( - 4)}^2} - 4(1)( - 4)} }}{{2(1)}} \\
x = \dfrac{{4 \pm \sqrt {16 + 16} }}{2} \\
x = \dfrac{{4 \pm \sqrt {32} }}{2} \\
x = \dfrac{{4 \pm \sqrt {16 \times 2} }}{2} \\
x = \dfrac{{4 \pm 4\sqrt 2 }}{2} \\
x = \dfrac{{2\left( {2 \pm 2\sqrt 2 } \right)}}{2} \\
x = 2 \pm 2\sqrt 2 \\
\]
Note: You must not simply add and subtract the arguments inside the log to solve these problems. Logs don’t work that way. For addition and subtraction of logs, you must use the above mentioned formulas. Logs are special terms in mathematics and hence, their addition, subtraction is quite different from others. If you do it the normal way, you will end up getting the wrong answers.
The very first step to solve these types of problems is to use the addition and subtraction log properties. We know that $\log a + \log b = \log (ab)$ and $\log a - \log b = \log \dfrac{a}{b}$. So, after using the given properties on the above question, we will get a much simplified version of the question. To move forward we will use the $\log a - \log b = \log \dfrac{a}{b}$ property and then move forward to equate the argument part inside the equation to 0. Solving the equation we will get our final answer.
Complete step by step solution:
The given question we have is ${\log _5}(x - 1) + {\log _5}(x - 2) - {\log _5}(x + 6) = 0$
Now, we will use a simple property of log, and that is
$\log a - \log b = \log \dfrac{a}{b}$
So, applying this rule to the question, the modified version of the question will be:-
$
{\log _5}(x - 1) + \left[ {{{\log }_5}(x - 2) - {{\log }_5}(x + 6)} \right] = 0 \\
{\log _5}(x - 1) + \left[ {{{\log }_5}\left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
$
Now, we will use another log property which states that:-
$\log a + \log b = \log (ab)$
So, when we use this property, our modified version of the question will be:-
$
{\log _5}(x - 1) + \left[ {{{\log }_5}\left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\left( {x - 1} \right) \times \left( {\dfrac{{x - 2}}{{x + 6}}} \right)} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\dfrac{{\left( {x - 1} \right)\left( {x - 2} \right)}}{{x + 6}}} \right] = 0
\\
\Rightarrow {\log _5}\left[ {\dfrac{{{x^2} - 2x - x + 2}}{{x + 6}}} \right] = 0 \\
\Rightarrow {\log _5}\left[ {\dfrac{{{x^2} - 3x + 2}}{{x + 6}}} \right] = 0 \\
$
To further simplify this step, we will use another property which states that:-
If,
$
{\log _b}a = x \\
\Rightarrow {b^x} = a \\
$
So, if we use this property on the above question, we will get:-
\[
{\log _5}\left[ {\dfrac{{{x^2} - 3x + 2}}{{x + 6}}} \right] = 0 \\
\Rightarrow {5^0} = \dfrac{{{x^2} - 3x + 2}}{{x + 6}} \\
\Rightarrow 1 = \dfrac{{{x^2} - 3x + 2}}{{x + 6}} \\
\Rightarrow x + 6 = {x^2} - 3x + 2 \\
\]
Subtracting x from both the sides we will get:-
\[
x + 6 = {x^2} - 3x + 2 \\
x + 6 - x = {x^2} - 3x + 2 - x \\
6 = {x^2} - 4x + 2 \\
\]
Subtracting 2 from both the sides we will get:-
\[
6 = {x^2} - 4x + 2 \\
6 - 2 = {x^2} - 4x + 2 - 2 \\
4 = {x^2} - 4x \\
\]
Subtracting 4 from both the sides we will get:-
\[
4 = {x^2} - 4x \\
4 - 4 = {x^2} - 4x - 4 \\
{x^2} - 4x - 4 = 0 \\
\]
To solve this step we will use the quadratic formula method \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
Here,
a=1
b=-4 and c=-4
so,
\[
x = \dfrac{{ - ( - 4) \pm \sqrt {{{( - 4)}^2} - 4(1)( - 4)} }}{{2(1)}} \\
x = \dfrac{{4 \pm \sqrt {16 + 16} }}{2} \\
x = \dfrac{{4 \pm \sqrt {32} }}{2} \\
x = \dfrac{{4 \pm \sqrt {16 \times 2} }}{2} \\
x = \dfrac{{4 \pm 4\sqrt 2 }}{2} \\
x = \dfrac{{2\left( {2 \pm 2\sqrt 2 } \right)}}{2} \\
x = 2 \pm 2\sqrt 2 \\
\]
Note: You must not simply add and subtract the arguments inside the log to solve these problems. Logs don’t work that way. For addition and subtraction of logs, you must use the above mentioned formulas. Logs are special terms in mathematics and hence, their addition, subtraction is quite different from others. If you do it the normal way, you will end up getting the wrong answers.
Recently Updated Pages
Class 11 Question and Answer - Your Ultimate Solutions Guide
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Physics: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Trending doubts
The reservoir of dam is called Govind Sagar A Jayakwadi class 11 social science CBSE
What problem did Carter face when he reached the mummy class 11 english CBSE
What organs are located on the left side of your body class 11 biology CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Petromyzon belongs to class A Osteichthyes B Chondrichthyes class 11 biology CBSE
Comparative account of the alimentary canal and digestive class 11 biology CBSE